The shaping stratum of the Markan passion narrative - Hombana, Mphumezi (Hervormde teologiese studies, 2023)
This study is an attempt to investigate the shaping stratum of the Markan passion narrative (PN). The ultimate focus is on discovering the factors behind the text of Mark that influenced the shaping of the passion account. Since early form criticism, there has been an assumed tradition of an early existing passion account prior to the Markan narrative, to which we do not have access in our contemporary world. However, this study argues that the PN is shaped not only by a tradition to which we do not have access, as argued by previous form critics but also perhaps by how one would describe any crucifixion in antiquity. As we possibly know, this could be true of any early tradition, including the PN in Mark. In other words, this paper is thus proposing a shift from a possible oral source (tradition) to general literary influences that shaped the Markan PN. This means we can see possible influences that determine what would be part of a narrative of a noble death from within Graeco-Roman and Jewish literary influences despite the fact that we cannot get hold of Mark’s traditional sources. This paper utilises historical criticism as the method to investigate the shaping stratum of the Markan PN.ContributionSo, an access to these literary influences serves as an adequate tool to aid the contemporary reader to adequately understand Mark’s PN as the death and resurrection of Jesus are the integral part in the whole story of Christianity. An understanding of this remarkable account is very significant for churches in Africa and worldwide too.